Computed tomography with normal chest radiograph in tuberculous infection. - Delacourt, C (1993)
Children with primary tuberculosis infection without disease must be identified and treated preventively to avoid an increase in the incidence of tuberculosis in children. However, the recognition of infected cases without disease is often difficult. In particular, minimal active disease may be present in many cases but unrecognised on chest radiography. Computed tomography was therefore performed in 15 children with tuberculous infection and a normal chest radiograph to measure the size of their mediastinal lymph nodes. Ten control children without tuberculosis were also evaluated. When compared with controls it was found that nine of 15 (60%) infected children had enlarged lymph nodes. Adenopathies were more frequent in infected children less than 4 years old than in those over 8 years old. The demonstration of unrecognised active disease in many infected children raises the question of the adequate treatment for these children. It is proposed that a two drug regimen would be more appropriate than isoniazid alone in these cases.